On the use of dexamethasone‐loaded liposomes to induce the osteogenic differentiation of human mesenchymal stem cells. (7th October 2013) - Monteiro, Nelson; Martins, Albino; Ribeiro, Diana; Faria, Susana; Fonseca, Nuno A.; Moreira, João N.; Reis, Rui L.; Neves, Nuno M.
Abstract: Stem cells have received considerable attention by the scientific community because of their potential for tissue engineering and regenerative medicine. The most frequently used method to promote their differentiation is supplementation of the in vitro culture medium with growth/differentiation factors (GDFs). The limitations of that strategy caused by the short half‐life of GDFs limit its efficacy in vivo and consequently its clinical use. Thus, the development of new concepts that enable the bioactivity and bioavailability of GDFs to be protected, both in vitro and in vivo, is very relevant. Nanoparticle‐based drug delivery systems can be injected, protect the GDFs and enable spatiotemporal release kinetics to be controlled. Liposomes are well‐established nanodelivery devices presenting significant advantages, viz. a high load‐carrying capacity, relative safety and easy production, and a versatile nature in terms of possible formulations and surface functionalization. The main objective of the present study was to optimize the formulation of liposomes to encapsulate dexamethasone (Dex). Our results showed that the optimized Dex‐loaded liposomes do not have any cytotoxic effect on human bone marrow‐derived mesenchymal stem cells (hBMSCs). More importantly, they were able to promote an earlier induction of differentiation of hBMSCs into the osteogenic lineage, as demonstrated by the expression of osteoblastic markers, both phenotypically and genotypically. We concluded that Dex‐loaded liposomes represent a viable nanoparticle strategy with enhanced safety and efficacy for tissue engineering and regenerative medicine. Copyright © 2013 John Wiley & Sons, Ltd.